MICROAGULHAMENTO E DRUG DELIVERY PARA TRATAMENTO DE ESTRIAS - FÖRSTER, LUIZA DAIANE; PAZZE, LAURA MORAIS; HARTMANN, DIANE DUARTE (Salão do Conhecimento, 2025)
MICROAGULHAMENTO E DRUG DELIVERY PARA TRATAMENTO DE ESTRIAS